Conference Report: Bioanalysis highlights from the 2012 American Association of Pharmaceutical Scientists National Biotechnology Conference. (September 2012) - Crisino, Rebecca M; Geist, Brian; Li, Jian
The American Association of Pharmaceutical Scientists (AAPS) is an international forum for the exchange of knowledge among scientists to enhance their contributions to drug development. The annual National Biotechnology Conference, organized by the AAPS on 21–23 May 2012 in San Diego, CA, USA, brings together experts from various disciplines representing private industry, academia and governing institutions dedicated toward advancing the scientific and technological progress related to discovery, development and manufacture of medical biotechnology products. Over 300 scientific poster presentations and approximately 50 oral presentation and discussion sessions examined a breadth of topics pertaining to biotechnology drug development, such as the advancement of vaccines and biosimilars, emerging and innovative technologies, nonclinical and clinical bioanalysis, and regulatory updates. This conference report highlights the existing challenges with ligand-binding assays, emerging challenges, innovative integration of various technology platforms and applicable regulatory considerations as they relate to immunogenicity and pharmacokinetic bioanalytical assessments.